2022
DOI: 10.22159/ijpps.2022v14i1.43145
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Rivastigmine Chitosan Nanoparticles for Neurodegenerative Alzheimer; In Vitro and Ex Vivo Characterizations

Abstract: Objective: In an attempt to optimize the anti-Alzheimer effect, rivastigmine-loaded chitosan nanoparticles were developed in order to target of brain through skin permeation. Methods: Rivastigmine-loaded chitosan-tripolyphosphate nanoparticles were prepared by modified ionic gelation method using tween 80 surfactants in different batches with variable chitosan/cross-linker ratios, desirability factors were applied to choose the optimal Nanocarrier and (F15) was selected. Different rivastigmine concentrations w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Tinctures with optical activity above the upper value (|α°|≥2.21°) of the interval were unstable dispersed systems with low values of the electrokinetic potential (|ξ|≪25mV), because of the presence of large unstable particles of the dispersed phase with sizes matching the micrometer range [10,16]. These particles interfered with polarimetric measurements, and they were also excluded from consideration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinctures with optical activity above the upper value (|α°|≥2.21°) of the interval were unstable dispersed systems with low values of the electrokinetic potential (|ξ|≪25mV), because of the presence of large unstable particles of the dispersed phase with sizes matching the micrometer range [10,16]. These particles interfered with polarimetric measurements, and they were also excluded from consideration.…”
Section: Resultsmentioning
confidence: 99%
“…The study of alcohol and water dilutions showed that the latter had greater stability. Water dilutions had electro kinetic potentials higher than the limiting values of the stability of the colloidal system (25 mV) [10,16] and reached-34 mV. It was reasonable to assume that stable nanoparticles in aqueous dilutions would freely penetrate cells (for example, due to pinocytosis) and transport biologically active substances.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan nanoparticles loaded with rivastigmine were used to target the brain through skin permeation [ 262 ]. Drug loading, ex-vivo skin permeation and kinetic studies were conducted to determine the stability over three months at different temperatures.…”
Section: Therapymentioning
confidence: 99%
“…Ex vivo studies revealed that the RVG-chitosan nanoparticles in gel formulae were not irritating to rat skin and had better skin permeation than chitosan nanoparticles’ aqueous dispersion. The chitosan nanoparticles also were capable of releasing RVG in a sustained manner and increasing the time release of the drug [ 262 ]. Another report compared liposomal formulations and observed that chitosan-coated liposomes have a better and longer release pattern than conventional liposomes.…”
Section: Therapymentioning
confidence: 99%
“…One of the main applications of nanotechnology is the nano-encapsulation of bioactive compounds for biological purposes. During the nano-encapsulation process, besides bioactive protection, their bioavailability also is improved due to an increase in the surface-to-volume ratio by reducing particle size into the nano-range [10].…”
Section: Introductionmentioning
confidence: 99%